Single-Phase Grid-Connected of PV Inverter Using PR Current Controller - Nor Su’aida, Yusof; Abu Zaharin, Ahmad (2017)
This paper presents a Proportional Resonant (PR) current controller applied to single-phase grid-connected of PV inverter with LCL filter. The damping resistor is adopted in LCL filter for restraining the high resonant peak value. In order to track a reference value with fast, the system with high gain is produced by the PR current controller in the wide range of frequency. Then, low THD of the yield grid current is compared with PI current controller.